Multimedia Information Technology and Applications: 21st International Conference on Multimedia Information Technology and Applications, MITA 2025, Jeju, South Korea, July 21–24, 2025, Proceedings (Communications in Computer and Information Science; Computer Science; Computer Science (R0), 2026)
This open access book constitutes the refereed proceedings of the 21st International Conference on Multimedia Information Technology and Applications, MITA 2025, Jeju, South Korea, during July 21–24, 2025. The 14 full papers and 5 short papers included in this book were carefully reviewed and selected from 94 submissions. They were organized in topical sections as follows: Artificial Intelligence for Multimedia. Multimedia System and Applications.